Pengaruh Kualitas Produk dan Harga terhadap Minat Beli Ulang pada Kerupuk Rambak NSR Bandung - Muhamad Sidik Ramdhan; Palupi Permataa Rahmi SP., M.Si; Dr. Erna Herlinawati, S.E., M.Si (Neolectura, 2023)
Competition in the business world has recently experienced very rapid development in line with developments in the globalization era. This can be seen from the increasing level of competition in the business world in marketing its products and services to consumers. Business people compete in marketing their products to be known and in demand by their consumers. This study aims to determine the effect of product quality and price on the intention to repurchase Crackers Rambak NSR Bandung. The research method used is descriptive and verification methods with a quantitative approach. The sampling technique used in this research uses probability sampling with simple random sampling technique with the study population consisting of 100 respondents determined using the slovin formula. The analysis used includes validity test, reliability test, classical assumption test, multiple regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. Repurchase intention is descriptively considered not good, descriptive quality is considered not good and price is considered not good. The results of the verification analysis of Product Quality on Repurchase Intention have a strong correlation, a determination value of 21.3% and Price has an effect on Repurchase Intention. Product Quality on Repurchase Interest has a very strong correlation value. The determination value is 51.7% and product quality affects purchase intention. Simultaneously Product Quality and Price affect Repurchase Intention, have a strong relationship and contribute 70.0%.